2015
DOI: 10.1108/prt-12-2013-0114
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and evaluation of nanosized mixed calcium iron oxide (CaFe2O4) as high heat resistant pigment in paints

Abstract: Purpose -The purpose of this paper was to prepare and evaluate a nanosized mixed calcium iron oxide as a high heat-resistant pigment. Heat-resistant pigments can be defined as chemical substances that impart color to a substrate or binder and retain their color and finish at elevated temperatures. Mixed metal oxides have been widely used as pigments in coating formulations. Design/methodology/approach -This work presents synthesis of nanosized calcium iron oxide as an inorganic pigment by using simple synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The peaks in the XRD pattern of calcium ferrite nanoparticles match with different phases of orthorhombic structure of calcium ferrite (post spinel—CaFe 2 O 4 and brownmillerite—Ca 2 Fe 2 O 5 ). The peaks at 24.92 (220), 29.24 (310), 31.98 (011), 33.43 (040), 41.29 (311), 43.52 (150), 49.33 (241) represent CaFe 2 O 4 (JCPDS: 50‐1746 and 72‐1199) while peaks at 33.00 (200), 46.60 (141), 52.40 (045), 57.89 (431), 59.23 (360) and 70.22 (282) correspond to Ca 2 Fe 2 O 5 (JCPDS: 71‐2264) . The XRD spectrum for GO shows a peak at 2θ = 10.47 (001) and 42.38 (100) characteristic of graphene oxide which disappears in the XRD patterns of CF/GO nanocomposite …”
Section: Resultsmentioning
confidence: 99%
“…The peaks in the XRD pattern of calcium ferrite nanoparticles match with different phases of orthorhombic structure of calcium ferrite (post spinel—CaFe 2 O 4 and brownmillerite—Ca 2 Fe 2 O 5 ). The peaks at 24.92 (220), 29.24 (310), 31.98 (011), 33.43 (040), 41.29 (311), 43.52 (150), 49.33 (241) represent CaFe 2 O 4 (JCPDS: 50‐1746 and 72‐1199) while peaks at 33.00 (200), 46.60 (141), 52.40 (045), 57.89 (431), 59.23 (360) and 70.22 (282) correspond to Ca 2 Fe 2 O 5 (JCPDS: 71‐2264) . The XRD spectrum for GO shows a peak at 2θ = 10.47 (001) and 42.38 (100) characteristic of graphene oxide which disappears in the XRD patterns of CF/GO nanocomposite …”
Section: Resultsmentioning
confidence: 99%
“…Art coating usually serves a decorative effect [ 1 , 2 , 3 ] but also has more robust protection than general coatings [ 4 , 5 ]. Studies [ 6 , 7 , 8 ] have shown that adding metal filler in the water-based coating and applying a modified art coating can lend the surface of buildings, furniture, and handicrafts a shiny metallic luster. Consequently, this modified coating provides a protective and decorative role to the applied products, causing an increase in added value [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pigments are accepted as the principal chemicals of coatings colours. In the literature, there are many studies conducted with the application of different pigments to the form of the coating process (Chinga and Helle, 2002;Morsy and El-Sherbiny, 2004;Fjellström et al, 2009;Aman, 2012;Arbatan et al, 2012;El-Sherbiny et al, 2014;Abd El-Wahab et al, 2015;Wahba et al, 2015;Morsy et al, 2016;Zhang et al, 2018;Ozcan and Tutak, 2020). Some are on the use and effects of natural and alternatively synthesised pigments in the surface coating of paper material.…”
Section: Introductionmentioning
confidence: 99%